Primary Biliary Cholangitis Associated with Ulcerative Colitis: Case Series and Literature Review - Qi Li; Ye Zong (Medicina)
Purpose: To study the coexistence of ulcerative colitis (UC) and primary biliary cholangitis (PBC). Methods: The Beijing Friendship Hospital patient database was explored to identify patients presenting both UC and PBC from January 2015 to July 2024. By a review of the literature, the characteristics of UC patients who experienced PBC was summarized. Results: We identified 890 UC patients and reported 4 individuals who suffered from UC and PBC. Compared to the general population, UC patients seem to have a higher risk of PBC. Only 28 cases of UC with PBC have been reported so far. Most patients were diagnosed with UC prior to PBC. Once UC patients are complicated with PBC, they might experience more than one extraintestinal manifestation (EIM). Shared susceptibility genes, certain bacterial infections, and common immune-mediated mechanisms may be involved in the pathogenesis of UC patients with PBC. Conclusions: Although the coexistence of UC and PBC is uncommon, PBC should be considered in UC patients with hepatobiliary disorders.